Desempenho da fixação biológica de nitrogênio em cultivares de feijão-caupi em Roraima - Melo, Shirlany Ribeiro de (2009)
The work aimed to evaluate the biological nitrogen fixation (BNF) in five cowpea cultivars - BR-17 Gurguéia, BRS Guariba, BRS Mazagão, UFRR Grão Verde and Pretinho Precoce 1. In 2007, one green house and one filed experiment were performed using a factorial design with five cowpea cultivars and three nitrogen sources (urea fertilization in the level of 50 kg ha-1 of N, inoculation with BR 3262 and BR 3267 Bradyrhizobium) and a complete control. Thirty-five days after plants emergency, were evaluated the nodules number and dry weight, plants dry weigh matter and total-N, nodular efficiency in the green house and the grains yield in field experiment on the harvest. In the green house, high nodulation and nodular efficiency were observed for both strains in all cultivars, with prominence to BR 17 Gurguéia and Pretinho Precoce 1, with the largest and smallest nodulation, respectively. The nodulation and total-N for all cultivars were smaller in the field, comparatively with the green house experiment, indicating the interference of local factors in the BNF. A grains yield increase was observed for all cultivars, in consequence of the inoculation, especially with the BR 3262 strain, that showed capacity to substitute the nitrogen fertilization. The results showed that cowpea cultivars recommended to Roraima have a good response to the inoculation with the strains evaluated showing that they are an efficient alternative to increase the yield of this crop, generating a positive economical and environmental impact to agriculture in Roraima.